Parlare di Letteratura ai Giovani: una Proposta Didattica - Greco, Miriam (Italogramma, 2025)
If we have a look to the data recorded by the Invalsi tests and the OECD Pisa surveys, what emerges is the significant difficulties among young people in approaching written texts, especially if they are literary works. How can Italian schools respond to this emergency? An answer seems to start from an analysis of youth slang. Only by starting from the world of the new generations it may be possible to plan educational activities that are capable of activating the attention and motivation of learners and of stimulating an active and effective learning process that gradually leads students towards the horizon of literary texts and their language. As evidenced by the data recorded by the Invalsi tests and the OECD Pisa surveys, young people seem to struggle with significant difficulties in approaching written texts, especially literary works. How can Italian schools respond to this critical situation? A first step in finding the answer could be an analysis of the language use of the youth. Only by starting out from the world of the new generations can we create educational activities that are capable of motivating young learners and promoting an active and effective learning process which can gradually guide them towards the horizon and language of literary texts.